Rekonseptualisasi Judicial Pardon Dalam Sistem Hukum Indonesia (Studi Perbandingan Sistem Hukum Indonesia Dengan Sisitem Hukum Barat) - Farikhah, Mufatikhatul (UI Scholars Hub, 2018)
Judicial Pardon in Indonesia is the result of comparative studies with several countries including the Netherlands, Greece, Portugal and Uzbekistan. The author tries to discover what legal system underlies the concept of Judicial Pardon applied in some countries and how the concept of judicial pardon is most compatible with the Indonesian Law System. This paper is based on normative legal research with a Historical Approach, Comparative Approach, and conceptual approach. Currently the criminal law is also influenced by the Anglo saxon legal system. Responding to the second issue is more appropriate when incorporating the conception of Islam as well as the customary court in its formulation, where there should be a clear formulation of any crime that can be given by the judges, so that the legal certainty is guaranteed and formulated in the RKUHAP into one type of decision that can be given by the judge for the forgiveness of a judge that is a guilty verdict without punishment.